Fuzzy-based coverage and capacity scheme in LTE heterogeneous networks. (17th November 2017) - Kuo, Yen-Wei; Chou, Li-Der
Abstract: Coverage and capacity optimization (CCO) is a crucial procedure in Long-Term Evolution (LTE) Self-Organizing Network (SON). In recent studies, fuzzy theory has been widely applied for CCO in centralized SON but not in distributed SON. Distributed SON can be applied in user-deployed small cells such as femtocells. In the present paper, a distributed, autonomous, and low-complexity fuzzy-based coverage and capacity scheme is proposed for LTE heterogeneous networks (HetNet). To accomplish this goal, the proposed scheme manages radio resources to minimize inter-cell interference. A tradeoff exists between cell coverage and capacity due to inter-cell interference. By leveraging three fuzzy memberships, the scheduling decision is adaptively made by a low-complexity intersection function. Different from conventional fuzzy approaches, the proposed approach does not depend on pre-defined fuzzy rules and pre-defined fuzzy membership models. System performance is evaluated in terms of throughput and energy efficiency. The simulation results show that the proposed approach improves system performance by up to about 39% compared with a joint optimization algorithm.